THE GROWTH RESPONSE AND YIELD OF CIPLUKAN DUE TO GIVING PALM OIL ASH IN PEAT SOIL - Maya dwiyanti; Iwan sasli; Siti hadijah (Jurnal Sains Pertanian Equator, 2019)
This study aims to determined the best dosage of palm oil ash on the growth and yield of ciplukan plants in peat soil. This study was conducted from 8th March 2019 – 8th June 2019 in the Faculty of Agriculture’s experimental garden, Tanjungpura University, Pontianak. This study uses a Completely Randomized Design (CRD) method by one factor oil palm ash treatment consisting of 5 treatment levels, with 5 replications and every treatment there are 4 plant samples, so there were 100 plants. This study has treatment such as: a1 = 10 tons/ha equivalent to 200 g/polybag, a2 = 15 tons/ha equivalent to 300 g/polybag, a3 = 20 tons/ha equivalent to 400 g/polybag, a4 = 25 equivalent to 500 g/polybag and a5 = 30 tons/ha equivalent to 600 g/polybag. The variables observed were plant height (cm), many of branches (branches), root volume (cm3), plant dry weight (g), number of fruits per plant (fruit) and weight of fruit per plant (g). The study  results show the of various dosage palm oil ash gave a significant effect on all variables. The best result dosage of palm oil ash  is 10 tons/ha equivalent to 200 g/polybag. Keywords: Ciplukan,Palm Oil Ash, Peat Soil